Facebook is no "Great equalizer": A big data approach to gender differences in civic engagement across countries. Issue Volume 35:Number 1(2017:Feb.)Special Issue (February 2017) - Brandtzaeg, Petter Bae
Facebook is expected to facilitate more equal participation in civic engagement across genders and countries. With the use of a big data tool (Wisdom), we explored gender disparities in various Facebook liking practices concerning expressions of civic engagement among 21, 706, 806 Facebook users in 10 countries across Asia, Africa, the Americas, and Europe. We observed distinct patterns with regard to civic and political expressions on Facebook, with males drawn more toward politically and information-oriented liking practices when compared to females. Moreover, females (aged 13–28 years) in Europe and the Americas are more likely than males to support humanitarian aid and environmental issues on Facebook. This latter finding was not evident in Asia and Africa, where males are more active in liking all forms of civic expressions on Facebook. In conclusion, this study shows that the gender differences in civic engagement that exist offline to a large degree are replicated and reinforced on Facebook.